Changes in monocyte subsets are associated with an increased risk of AAA and are surrogate markers for AAA morphology in patients with late-stage disease - Hamann, Bianca; Klimova, Anna; Kapalla, Marvin; Poitz, David M.; Busch, Albert; Morawietz, Henning; Reeps, Christian; Hofmann, Anja (Frontiers in Immunology, 2025)
IntroductionMonocytes play a role in the pathology of abdominal aortic aneurysm (AAA) and can display immunophenotypic heterogeneity. Alterations in monocyte subsets are associated with cardiovascular risk, but their profile in AAA is poorly understood.AimWe aimed to comprehensively define associations of monocyte phenotypes with AAA risk and AAA morphology.MethodsMonocyte subsets (CD14++CD16−, CD14++/CD16+, and CD14+/CD16++) were analyzed in an observational study in patients with AAA (n = 33) and varicose veins (n = 33) using flow cytometry.ResultsClassical monocytes were 3% lower (p = 0.001) in AAA, while intermediate and non-classical monocytes were 1.8-fold (p = 0.019) and 1.9-fold (p = 0.025) higher in AAA, respectively. The differences remained significant after adjusting for age, sex, and peripheral artery disease. A decrease in classical monocytes [odds ratio (OR): 0.73, p = 0.002] and increases in intermediate (OR: 1.41, p = 0.006) and non-classical monocytes (OR: 1.54, p = 0.030) were associated with a higher risk of AAA. Non-classical monocytes showed an inverse correlation with AAA diameter (rP = −0.64, p = 0.001) and AAA volume (rP = −0.50, p = 0.003).ConclusionThe present study revealed age- and sex-independent shifts in monocytes, all of which were associated with the risk of AAA disease. Non-classical monocytes were inversely correlated with AAA diameter and volume and thus may be surrogate markers for AAA morphology.